Pengaruh Pendekatan Pembelajaran Pendidikan Matematika Realistik Indonesia (PMRI) dengan Mobile Learning terhadap Kemampuan Komunikasi Matematis Siswa - Swastyka Rakhma Wiyanti; Rina Marlina; Dori Lukman Hakim (Logaritma : Jurnal Ilmu-ilmu Pendidikan dan Sains, 2021)
This research is motivated by the low mathematical communication skills of students in one of the junior high schools in Karawang Regency. This research was conducted with the aim of knowing whether the learning approach of Indonesian Realistic Mathematics Education (PMRI) with Mobile Learning has an effect on Students' Mathematical Communication Ability. The research approach used in this study is a quantitative approach with experimental methods and a Posttest Only One Control Group research design conducted at NURUL FALAH Junior High School JAKARTA. The data was collected using a mathematical communication ability test instrument and the hypothesis test used was an analysis of the difference between two averages (2 Independent Sample t-test) to determine the average difference in mathematical communication skills of experimental class students using the PMRI learning approach with mobile learning. and a control class that uses a direct learning approach with mobile learning. The calculation of the data was carried out using the SPSS ver 22 (Statistical Product and Service Solution) application and based on the calculation of the posttest results of the two groups, there were differences in students' mathematical communication skills.